Theories of development contentions, arguments, alternatives - Peet, Richard (New York Guilford Press, 2009)
Widely adopted, this unique text critically evaluates the leading theories of international economic development, from classical economic and sociological models to Marxist, poststructuralist, and feminist perspectives. No other book provides such comprehensive coverage or links the theories as incisively to contemporary world events and policy debates. Reexamining neoliberal conceptions of economic growth, the authors show what a more just and democratic form of development might look like today.
Includes bibliographical references (p. 292-313) and index.
Keywords: Economic development